The influence of labor remuneration on employee loyalty to the firm - Tuoi, Do Thi; Hong, Nguyen Thi; Phuong, Tran Thi Minh; Hung, To Xuan (Edelweiss Applied Science and Technology, 2025)
This study uses social exchange theory and psychological contract theory for the purpose of evaluating and measuring the influence of labor remuneration on employee loyalty to the firm. Through a survey of commercial and tourism firms in Hanoi, we employ quantitative research methods with the support of SPSS software. We utilize techniques including the analysis of the reliability of scales using the Cronbach alpha coefficient, EFA analysis, correlation analysis, and linear regression. The research results indicate that the influence of five selected factors is statistically significant, while one factor has no influence on the dependent variable. The level of influence, in decreasing order, is salary, job content, financial benefits, training and development opportunities, and working environment. Consequently, the study proposes several recommendations on financial and non-financial remuneration to enhance employee loyalty to the firm. The research results also contribute to supporting firm leaders in making decisions regarding employee retention and improving the quality of human resources.